Attenuation of hypotensive effect of propranolol and thiazide diuretics by indomethacin. Issue 6242 (13th September 1980) - Watkins, J; Abbott, E C; Hensby, C N; Webster, J; Dollery, C T
Abstract : The effects of 100 mg indomethacin daily for three weeks on blood pressure and urinary excretion of prostaglandin F2 alpha were studied in a double-blind, placebo-controlled comparison of two groups of patients with essential hypertension, eight receiving propranolol and seven thiazide diuretics. Compared with placebo, adding indomethacin to the patients' established antihypertensive treatment increased blood pressure by 14/5 Hg supine and 16/9 mm Hg erect in the patients receiving propranolol, and by 13/9 mm Hg supine and 16/9 mm Hg erect in the patients receiving thiazide diuretics (all p less than or equal to 0.05). The excretion of the major urinary metabolite of prostaglandin F2 alpha was reduced by 67% in the propranolol-treated patients and by 57% in those receiving a thiazide diuretic. Body weight increased by 0 . 8 kg (propranolol) and 1 . 1 kg (thiazide diuretic) when indomethacin was given, but there were no significant changes in creatinine clearance, urinary sodium excretion, or packed cell volume in either treatment group. These results suggest that products formed by the arachidonic acid cyclo-oxygenase contribute to the regulation of blood pressure during treatment with both propranolol and thiazide diuretics. Inhibition of the cyclo-oxygenase with indomethacin partially antagonises the hypotensive effect of these drugs.